Isolated Tuberculosis of Capitate and Triquetrum - Karakaplan, Mustafa; Köroğlu, Muhammed; Ergen, Emre; Aslantürk, Okan; Özdemir, Zeynep Maraş; Ertem, Kadir (Journal of Wrist Surgery, 2017)
Musculoskeletal system is involved in about 20% of the patients diagnosed with tuberculosis. Although musculoskeletal tuberculosis generally affects spine and large joints (hip and knee), hand involvement of the tuberculosis is seen in 10% of the patients with musculoskeletal involvement and also isolated tuberculosis of hand or wrist is much rarer.In the following report, we discuss the case of a 23-year-old male patient who was diagnosed with isolated tuberculosis of the capitate and triquetrum bone. The patient presented with a nonhealing sinus on the left wrist joint. Imaging revealed lytic lesions of the capitate and triquetrum. The diagnosis of tuberculosis was confirmed by histopathological examination on the bone specimen obtained from the debridement and curettage. Antituberculosis therapy was started postoperatively and 1 month later, healing of the sinus was observed. There was no sign of reactivation seen at follow-up 22 months after treatment.
Keywords: tuberculosis; wrist; capitatum; triquetrum